How Much Cardiopulmonary Resuscitation Does a Pediatric Emergency Provider Perform in 1 Year? A Video-Based Analysis. Issue 7 (July 2020) - Donoghue, Aaron; Abbadessa, Mary Kate; Hsieh, Ting-Chang; Frankenberger, Warren; Myers, Sage
Abstract : Objectives: We aimed to quantify time performing chest compressions (CCs) per year of individual providers in a pediatric ED and to project a rate of opportunity for CC based on median clinical hours per provider category. Methods: This was an observational study of video-recorded resuscitations in a pediatric ED over 1 year. Events where CCs were performed for more than 2 minutes were included. Identification of providers and duration of CCs per provider were determined by video review. Time of CCs was totaled per provider over the study period. Data were expressed as median and interquartile range (IQR). Rate of opportunity for providing CC to a child was calculated by dividing the median clinical hours per year per provider type by the number of CC events per year. Results: Twenty-three CC events totaling 340 minutes of CCs were analyzed. Chest compressions were performed by 6 (13%) of 45 attending physicians, 3 (25%) of 12 fellows, 32 (22%) of 143 nurses, and 19 (59%) of 32 technicians. The median amount of time performing CC was 182 seconds (IQR, 91–396 seconds); by provider category, median amount of time was as follows: attending physicians, 83 seconds (IQR, 64–103 seconds); fellows, 45 seconds (IQR, 6–83 seconds); nurses, 128 seconds (IQR, 93–271 seconds); and technicians, 534 seconds (IQR, 217–793 seconds). The projected hours needed for an opportunity to perform CCs was 730 hours (91 shifts) for attending physicians, 243 hours (30 shifts) for fellows, and 1460 hours (121 shifts) for nurses and technicians. Conclusions: Performing CCs on children in the ED is a rare event, with a median of 3 minutes per provider per year. Future studies should determine training methods to optimize readiness for these rare occurrences.